Microbial removal mechanism of chromium and cadmium by humic acid-loaded nano zero-valent iron prepared by liquid-phase reduction method - Liu, Zhiyi; Zhao, Xuan; Yang, Jianwei; Chen, Xi; Cai, Yubing; Shaaban, Muhammad; Peng, Qi-an; Cai, Yajun (Frontiers in Plant Science, 2025)
Heavy metal pollution is a global issue that has drawn significant attention due to its environmental and health risks. This thesis focuses on the research of highly toxic chromium and cadmium in the environment. It explores the removal mechanism of Cr and Cd contamination using humic acid-loaded nano-zero-valent iron (NZVI@HA) prepared through a liquid-phase reduction method. Additionally, it investigates the interaction mechanism of removing Cr and Cd contamination by synergizing with the Chromium and Cadmium Symbiotic Bacterial Colony (NZVI@HA+Cr/CdMC). The findings indicate that NZVI@HA exhibited optimal removal efficiency for Cr(VI) at pH=2 (85.7%) and Cd(II) at pH=8 (94.8%). The initial concentration of Cr and Cd pollution showed an inverse relationship with the removal rates of Cd(II) and Cr(VI). Moreover, the reaction temperatures were positively correlated with the removal rates of Cd(II) and Cr(VI). Cu2+ significantly enhanced Cr(VI) removal in the water column (p<0.01), whereas Zn2+ notably inhibited Cd(II) removal (p<0.05). In the NZVI@HA+Cr/CdMC system, extracellular polymers (EPS), tyrosine, and tryptophan, through van der Waals forces, facilitated the removal of Cd(II) and Cr(VI) complexation. This reduced the stress of Cr(VI) and Cd(II) on Cr/CdMC, thereby enhancing the removal of Cr(VI) and Cd(II).